Analysis of Early Childhood Arabic Language Acquisition of The Komunitas Anak Shalih Based on CEFR - Rozaanah, Rozaanah (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2024)
Early age is a golden opportunity for children; therefore, early age is called the golden age for children. At this age, the child has extraordinary abilities, so it is good to be developed optimally. It is the golden age for the child to learn and acquire the language without neglecting other aspects. This is done in Komunitas Anak Shalih Tanjung Morawa. While in the Komunitas Anak Shalih, early childhood children at the educational institution are familiarised with hearing the names of objects and conveying them using Arabic. But in the acquisition of Arabic, they do not have a framework standardisation as a reference. Let's call it one of the CEFR. This study will answer questions related to the process of acquiring Arabic for early childhood in the Komunitas Anak Shalih and their speaking skills according to CEFR levels. This study uses a qualitative naturalistic approach using an embedded case study design model or case study. Data collection techniques are observation, interviews, and documentation, with data analysis to reduce data, present data, draw conclusions, and verify. The results found that early childhood language acquisition in the Komunitas Anak Shalih used behaviourism theory, and their speaking skills were at the rudimentary A1 level (PreA1) based on the CEFR.